Interdisciplinary Management of Cystic Neoplasms of the Pancreas - Linda S. Lee; Thomas Clancy; Vivek Kadiyala; Shadeah Suleiman; Darwin L. Conwell (Gastroenterology Research and Practice)
Cystic neoplasms of the pancreas are increasingly recognized due to the frequent use of abdominal imaging. It is reported that up to 20% of abdominal cross-sectional scans identify incidental asymptomatic pancreatic cysts. Proper characterization of pancreatic cystic neoplasms is important not only to recognize premalignant lesions that will require surgical resection, but also to allow nonoperative management of many cystic lesions that will not require resection with its inherent morbidity. Though reliable biomarkers are lacking, a wide spectrum of diagnostic modalities are available to evaluate pancreatic cystic neoplasms, including radiologic, endoscopic, laboratory, and pathologic analysis. An interdisciplinary approach to management of these lesions which incorporates recent, specialty-specific advances in the medical literature is herein suggested.